Abdominal adiposity, body composition and survival after liver transplantation. Issue 3 (13th February 2016) - Terjimanian, Michael N.; Harbaugh, Calista M.; Hussain, Adnan; Olugbade, Kola O.; Waits, Seth A.; Wang, Stewart C.; Sonnenday, Christopher J.; Englesbe, Michael J.
Abstract: Background: Current measures of obesity do not accurately describe body composition. Using cross‐sectional imaging, objective measures of musculature and adiposity are possible and may inform efforts to optimize liver transplantation outcomes. Methods: Abdominal visceral fat area and psoas muscle cross‐sectional area were measured on CT scans for 348 liver transplant recipients. After controlling for donor and recipient characteristics, survival analysis was performed using Cox regression. Results: Visceral fat area was significantly associated with post‐transplant mortality (p < 0.001; HR = 1.06 per 10 cm 2, 95% CI: 1.04–1.09), as were positive hepatitis C status (p = 0.004; HR = 1.78, 95% CI: 1.21–2.61) and total psoas area (TPA) (p < 0.001; HR = 0.91 per cm 2, 95% CI: 0.88–0.94). Among patients with smaller TPA, the patients with high visceral fat area had 71.8% one‐yr survival compared to 81.8% for those with low visceral fat area (p = 0.15). At five yr, the smaller muscle patients with high visceral fat area had 36.9% survival compared to 58.2% for those with low visceral fat area (p = 0.023). Conclusions: Abdominal adiposity is associated with survival after liver transplantation, especially in patients with small trunk muscle size. When coupled with trunk musculature, abdominal adiposity offers direct characterization of body composition that can aid preoperative risk evaluation and inform transplant decision‐making.